HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN PERKEMBANGAN BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS PADANGSARI KOTA SEMARANG - Oktiyani Puspita Sari; SA Nugraheni; M. Zen Rahfiludin (Jurnal Kesehatan Masyarakat (Undip), 2015)
Babies were experiencing in developmental process affected by several factors, one of which is exclusive breast fed. However, according to the report has exclusive breastfeeding in the Puskesmas Padangsari 2014 only amounted to 30%. The purpose of this study was to know the correlations of exclusive breastfeeding and 0-6 months baby's development gross motoric, fine motoric, language/cognitive, and social in Puskesmas Padangsari Semarang. This study was an analytical study with the cross-sectional design. The development was assessed using a summary of the questionnaire development DDST (Denver Development Screening Test), with a sample size of 51 babies according to inclusion criteria. Statistical analysis chi square test showed exclusive breastfeeding was 31,4%. The results showed exclusively breastfed infants have evolved according to age as follows: 62.5% of gross motor, fine motor 68.7%, language / cognitive 81.2%, and 56.2% social. For those who are not exclusively breast-fed had been developed according to age is as follows: 82.8% of gross motor, fine motor 65.7%, language / cognitive 45.7%, and 54.2% social. This study shows that there is a correlation between exclusive breastfeeding with the development of language / cognitive infants aged 0-6 months (p˂0,05). There was no correlation of exclusive breastfeeding with the development of gross motor, fine motor, and social infants aged 0-6 months (p˃0,05)